2015
DOI: 10.4137/cmed.s26045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Habitual Khat Chewing on Glycemic Control, Body Mass Index, and Age at Diagnosis of Diabetes in Patients with Type 2 Diabetes Mellitus in Yemen

Abstract: Khat chewing is common in Yemen. We conducted this study to see if it affected diabetes control in patients with type 2 diabetes mellitus (DM). We studied 1540 patients with type 2 DM attending an endocrinology clinic in Sana’a, Yemen, of which 997 were khat chewers (KC) and 543 were non-khat chewers (NKC). The patients answered a questionnaire regarding khat chewing. Hemoglobin A1c (HbA1c) and body mass index (BMI) were measured. KC had a higher mean HbA1c of 9.8 (95% confidence interval (95% CI) 9.6–10) than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 17 publications
4
20
1
1
Order By: Relevance
“…Many people chew it on a daily basis, mostly in the afternoon and evening periods, and among our patients (mostly from Sana'a and the surrounding areas), khat chewing was only mildly affected by the war among the patients coming to our clinic, with 94.9% of the males and 87.5% of the females who were khat chewers before the war continuing to chew khat after the war, even though their income had decreased. In our study, the numbers of patients who chewed khat before the war was similar to what we had shown in a previous study, with over 50% of the females and almost 80% of the males being regular chewers [23]. Most of the patients that continued to follow up in our clinic after the war started were probably better off economically than the patients who discontinued follow up, since this was a private clinic where patients had to pay for the doctor's visit.…”
Section: Discussionsupporting
confidence: 90%
“…Many people chew it on a daily basis, mostly in the afternoon and evening periods, and among our patients (mostly from Sana'a and the surrounding areas), khat chewing was only mildly affected by the war among the patients coming to our clinic, with 94.9% of the males and 87.5% of the females who were khat chewers before the war continuing to chew khat after the war, even though their income had decreased. In our study, the numbers of patients who chewed khat before the war was similar to what we had shown in a previous study, with over 50% of the females and almost 80% of the males being regular chewers [23]. Most of the patients that continued to follow up in our clinic after the war started were probably better off economically than the patients who discontinued follow up, since this was a private clinic where patients had to pay for the doctor's visit.…”
Section: Discussionsupporting
confidence: 90%
“…19 However, two studies carried out in Yemen found that khat chewing increased the blood glucose levels in patients with T2DM. 15,18…”
Section: Khat and Glycemic Controlmentioning
confidence: 99%
“…14 There is growing evidence of the effect of khat chewing on T2DM and glycemic control. [15][16][17][18][19] However, the role of khat chewing in T2DM is not fully understood. Up to our knowledge, very few published papers have tried to draw a conclusion about khat chewing and it effect on T2DM and glycemic control.…”
Section: Introductionmentioning
confidence: 99%
“…However, khat chewers with type-2 diabetic mellitus showed higher mean body weight compared to non-chewer diabetic patients [83] . Data from both cross-sectional studies lacked previous nutritional history as well as family history of obesity.…”
Section: Khat and Obesitymentioning
confidence: 99%